7+2(x-3)-4x=

Simple and best practice solution for 7+2(x-3)-4x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+2(x-3)-4x= equation:


Simplifying
7 + 2(x + -3) + -4x = 0

Reorder the terms:
7 + 2(-3 + x) + -4x = 0
7 + (-3 * 2 + x * 2) + -4x = 0
7 + (-6 + 2x) + -4x = 0

Combine like terms: 7 + -6 = 1
1 + 2x + -4x = 0

Combine like terms: 2x + -4x = -2x
1 + -2x = 0

Solving
1 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -2x = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -2x = 0 + -1
-2x = 0 + -1

Combine like terms: 0 + -1 = -1
-2x = -1

Divide each side by '-2'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| y+1(9+24)-28=96 | | 5x+20=5x-18 | | 10+a=26 | | x(7x+5)-x(x)(x)=0 | | 5x^2+10x+8y^2-48y+37=0 | | 2(113-2c)+4c=226 | | 20+10x-(8x-12)=68 | | .03x+.07(18000-x)=90 | | 4k-(-6)=-2-(-16)-(-2) | | 6n-.7=11 | | 10+n=25 | | -18x^2+51x+8=0 | | X^2+6x+64=48 | | 9x^4-64=0 | | 4c^2+7x-15=0 | | 15+n=6 | | 3x^4-7x^2=0 | | (4x+2)-x=(2x-10) | | 9(2+v)+35v=14v | | .5x(x+4)=16 | | 69=12 | | 2a+4b=226 | | 8(4+v)+34v=14v | | -2.3q+16=-5q-3 | | x^2+6x-24.01=0 | | 10*x+4=12*x-16 | | 3+2(x-1)=4x | | 3+2n-6=25 | | 8z+11=7z+5 | | 4(12n-6)=6(-4+5n)+18n | | 2x-2.8-2.4x+2.6x-5= | | 6(-3-x)-2*x=14 |

Equations solver categories